Impacts of COVID-19 on Tourism in Bar Harbor, Maine - Gabe, Todd (Maine Policy Review, 2021)
This paper examines the effects of COVID-19 on tourism in Bar Harbor, Maine. The analysis considers four channels by which the pandemic affected Bar Harbor: (1) reduction in overnight visitors, (2) decrease in Acadia National Park users, (3) cancellation of the 2020 cruise ship season, and (4) a national effect related to trends in overall US restaurant sales. The relative impacts of these four factors on Bar Harbor restaurant sales varied widely by month: the reduction in overnight tourists explains 40 percent of the overall decline; the national effect is associated with 35 percent of Bar Harbor’s decline; the cancellation of all cruise ship visits in 2020 explains 11 percent; and the reduction in the number of Acadia National Park users is responsible for 14 percent of the decline in restaurant sales in 2020. Knowing more about the channels by which COVID-19 affected hospitality sales in Bar Harbor can help state and local officials with recovery efforts and support tourism along the Maine coast.